Population frequencies of three DNA alleles linked to the Duchenne muscular dystrophy gene. Issue 6 (June 1989) - Papiha, S S; Roberts, D F; Clarke, A; Burn, J; Gardner-Medwin, D; Bhattacharya, S S
Abstract : To enquire whether the known X linked probes linked to the Duchenne muscular dystrophy gene vary in their RFLP frequencies, three probes, 754, XJ1.1, and pERT87.8, were tested in European, Indian Muslim, and West African samples. Though the average heterozygosity for the three together is fairly similar in the three populations, significant differences in allele frequencies were evident.